Analisis Hambatan dalam Kemampuan Membaca Permulaan pada Anak Usia Dini di Taman Kanak-Kanak Al-Mukaddimah Kota Pontianak - Qarmia Amanda; Sudarti Sudarti; Iin Maulina (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
This study aims to analyze the barriers in early childhood reading skills at Al-Mukaddimah Kindergarten. The main focus of this research includes identifying barriers experienced by children, factors that influence these barriers, and teacher efforts in overcoming reading difficulties. The method used is descriptive qualitative with a case study approach, which involves observation, interviews and documentation. The results show that there are several barriers in early reading skills, such as difficulty recognizing letters, distinguishing letters, and understanding symbols and numbers. Factors that influence these obstacles include the child's psychological condition, family environment, and learning methods applied by the teacher. Teachers' efforts in overcoming these obstacles are carried out through a fun and interactive approach, including the use of interesting learning media and varied teaching strategies. This research is expected to contribute to the development of reading learning methods in early childhood and provide recommendations for teachers and parents in supporting children's reading skills.